Acrylamide replaced by moringa extract in sugar production - Costa, Gustavo Henrique Gravatim; Freita, Cristhyane Millena De; Mendes, Franciele Quintino; Roviero, Juliana Pelegrini; Mutton, Márcia Justino Rossini (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2018)
AbstractThis manuscript showed a new product that can be used in sugar and alcohol production to replace the acrylamide polymer, applied in the juice treatment. This new product is an organic extract obtained from moringa seeds, which present the flocculating protein 2S-Albumin. This biomolecule is added in the decanter together with the limed and heated juice, increasing the sedimentation speed of impurities that, if remain in the process, decrease the quality of the obtained sugar. This issue is of great importance because the acrylamide molecule has carcinogenic and neurotoxic action in humans and may be incorporated within the sugar crystal or the mud (filter-cake) used as a fertilizer. Furthermore, it should be noted that this manuscript presents the best technique to extract the S-Albumin protein from moringa seeds (using a CaCl2 solution 0.1 mol/L), the best dosage to apply in the sugarcane juice (1300 mg/L), and similary sugar quality achieved, compared with the process using the acrylamide polymer.
Keywords: Moringa oleifera Lamarck; crystallization; sucrose; simple liming; S-albumin